The Effect of Cognitive Reappraisal on Reactive Aggression: An fMRI Study - Jiang, Qi; Hou, Lulu; Wang, Huanzhen; Li, Changran (Frontiers in Psychology, 2018)
A number of empirical researches have shown that reactive aggression, which is the behavior that is impulsive, thoughtless, driven by anger, and causes harm toward another individual, can lead to a series of negative effects. Cognitive reappraisal may have the potential to reduce reactive aggression, but evidence for this effect in healthy populations is lacking. We randomly assigned participants to a Reappraisal Group (n = 19) or Control Group (n = 20) in a functional magnetic resonance imaging (fMRI) version of the well-established Taylor Aggression Paradigm (TAP). TAP was employed to elicit and measure reactive aggression, during which participants were informed that they would play a competitive reaction time task against two opponents in turn and the winner would punish the loser. The TAP used in this study separates the decision-making (during which participants were asked to set a punishment level for the opponent) and affective processes (during which the punishment was applied or received) that underlie reactive aggression. Behavioral data showed that there was no difference between the Reappraisal Group and Control Group in the punishment level selections (i.e., reactive aggression). However, on the neural level, cognitive reappraisal reduced the activation of left insula, right cuneus, and right middle frontal gyrus (MFG) during the decision phase, independently of the level of provocation. In addition, cognitive reappraisal reduced the activation of the caudate under the provocative condition when making decisions about aggressive behavior. The results of the outcome phase showed that, after winning a competition, cognitive reappraisal increased the activation of the right orbital middle frontal gyrus (OMFG) under the provocative condition and reduced the activation of the bilateral supplementary motor area (SMA) under the non-provocative condition. The results suggest that cognitive reappraisal would be effective in modulating the neural activity of reactive aggression.